KINERJA LEMBAGA ZAKAT DALAM PEMBERDAYAAN UMMAT (Studi pada Web Dompet Dhuafa, Lazis NU dan Lazis Muhammadiyah) - Muhammad Munadi; Muslimah Susilayati (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2016)
This paper aims to describe the performance of zakat organizations for global empowerment (umma). The subjects of the study are three zakat organizations namely Dompet Dhuafa (DD), Lazis Nahdlatul Ulama (LAZISNU) and Lazis Muhammadiyah (LazisMU). Qualitative approach using content analysis is used to analyse the Data. The official websitesof those three zakat institution are used as primary sources. The results showed that the performance of Dompet Dhuafa is distinguished for its detail in the preparation of the vision, mission, goals, programs and organizational structures.Dompet Dhuafa develops the main program then makes it into specific program in details. There is relationship between vision, mission and objectives to reach both the local and global performance. LAZISMU is distinctive in optimizing the website. It can be foundthrough the use of four languages on the website: Bahasa Indonesia, Arabic, English, and France.LazisNU has outlined its program not only in the management of zakat, but also the empowerment.